Cytoglobin overexpression facilitates proliferation and migration of vascular smooth muscle cells - Li Lei; Xie Yilin; Li Shen; Tan Juanjuan; Qin Yingchun; Yan Zhiqiang (Archives of Biological Sciences, 2020)
Cytoglobin, a recently discovered globin, is expressed in vascular smooth muscle cells (VSMCs). Loss of cytoglobin provides a protective effect on vascular reconstruction but the effect of its overexpression is unclear. The aim of the study was to investigate the effect of cytoglobin overexpression on the migration and proliferation of VSMCs and possible mechanisms. We detected the expression of cytoglobin in hypertensive and normotensive rat aortas, with negative feedback regulation between cytoglobin and hypertension observed. The expression of cytoglobin was significantly decreased in hypertensive rats compared to normotensive rats, but VSMCs overexpressing cytoglobin displayed increased cell migration and proliferation, which led to a phenotypic switch. The increased expression of matrix metalloproteinase 9 and collagen Ia suggests a role for cytoglobin in extracellular matrix remodeling. Increased expression of proliferating cell nuclear antigen and decreased expression of p27 implies that cytoglobin is involved in modulating VSMC proliferation. Our findings indicate that cytoglobin may play an important role in vascular wall remodeling.